The fifth data release of the Kilo Degree Survey: multi-epoch optical/NIR imaging covering wide and legacy-calibration fields - Wright, Angus; Kuijken, Konrad; Hildebrandt, Hendrik; Radovich, Mario; Bilicki, Maciej; Dvornik, Andrej; Getman, Fedor; Heymans, Catherine; Hoekstra, Henk; Li, Shun-Sheng; Miller, Lance; Napolitano, Nicola R.; et al. (Astronomy and astrophysics, 2024)
We present the final data release of the Kilo-Degree Survey (KiDS-DR5), a public European Southern Observatory (ESO) wide-field imaging survey optimised for weak gravitational lensing studies. We combined matched-depth multi-wavelength observations from the VLT Survey Telescope and the VISTA Kilo-degree INfrared Galaxy (VIKING) survey to create a nine-band optical-to-near-infrared survey spanning 1347 deg2. The median r-band 5σ limiting magnitude is 24.8 with median seeing 0.7″. The main survey footprint includes 4 deg2 of overlap with existing deep spectroscopic surveys. We complemented these data in DR5 with a targeted campaign to secure an additional 23 deg2 of KiDS- and VIKING-like imaging over a range of additional deep spectroscopic survey fields. From these fields, we extracted a catalogue of 126 085 sources with both spectroscopic and photometric redshift information, which enables the robust calibration of photometric redshifts across the full survey footprint. In comparison to previous releases, DR5 represents a 34% areal extension and includes an i-band re-observation of the full footprint, thereby increasing the effective i-band depth by 0.4 magnitudes and enabling multi-epoch science. Our processed nine-band imaging, single- and multi-band catalogues with masks, and homogenised photometry and photometric redshifts can be accessed through the ESO Archive Science Portal.